Urinary Microbiome and Psychological Factors in Women with Overactive Bladder - Wu, Peng; Chen, Yang; Zhao, Jie; Zhang, Guihao; Chen, Jiawei; Wang, Junpeng; Zhang, Huijian (Frontiers in Cellular and Infection Microbiology, 2017)
Objectives: Emerging evidence indicates that alterations to the urinary microbiome are related to lower urinary tract symptoms. Overactive bladder (OAB) is a common disorder with complex etiologies and usually accompanied by psychological diseases. More information concerning the urinary microbiome and psychological factors in OAB is required. The aim of this study was to characterize the female urinary microbiome associated with OAB and investigate the relationships between urinary microbiome and psychological factors. Methods: Thirty women with OAB and 25 asymptomatic controls were recruited and asked to finish the Overactive Bladder Symptom Score, Self-Rating Anxiety Scale and Self-Rating Depression Scale. Urine specimens were collected by transurethral catheterization and processed for 16S rRNA gene sequencing using Illumina MiSeq. Sequencing reads were processed using QIIME. LEfSe revealed significant differences in bacterial genera between controls and OAB patients. The relationships between the diversity of the urinary microbiome and psychological scores were identified by Pearson’s correlation coefficient. Results: We found that bacterial diversity (Simpson index) and richness (Chao1) were lower in OAB samples compared to controls (P both = 0.038). OAB and control bacterial communities were significantly different (based on weighted UniFrac distance metric, R = 0.064, P = 0.037). LEfSe demonstrated that 7 genera were increased (e.g., Proteus and Aerococcus) and 13 were reduced (e.g., Lactobacillus and Prevotella) in OAB group compared to controls. There were negative correlations between scores on Self-Rating Depression Scale and both richness (Chao1, r = -0.458, P = 0.011) and diversity (Shannon index, r = -0.516, P = 0.003) of urinary microbiome in OAB group. Some bacterial genera of OAB women with anxiety or depression were significantly different from those without. Conclusions: The aberrant urinary microbiome with decreased diversity and richness may have strong implications in pathogenesis and treatment of OAB. Psychological conditions were correlated with characteristics of urinary microbiome in women with OAB. Further research is needed to understand the connection between central nervous system and urinary microbiome.